Três mulheres sob três visões: personagem feminina e ponto de vista em três contos de Guimarães Rosa - Júlia Soares Fernandes Matoso (2020)
This work proposed the alalisys of three female characters from three tales of Guimarães Rosa: Flausina, from “Esses Lopes” and Senhora/Sinhá, from “Sinhá Secada”, both from Tutaméia; and Mula-Marmela, from “A benfazeja”, tale from Primeiras estórias. In this study we consider: the woman’s social position in the social structure of the sertão of Guimarães Rosa, the characters constitution while they are studied as modern characters, and the way how their specificities are built by the narrator in each tale. We fundament the notion of Modernity on investigations like Hall (2011), Bradbury & McFarlane (1989), Hollington (1989), McFarlane (1989), Candido (1976), Barbosa (1990) and Moreira (2012). For the study of the social structure of the sertão of Guimarães Rosa, we had the aid of investigations like Gilberto Freyre (1987), Antonio Candido (1951), as well as the rosian critic which discusses the subject, like the ones from Luiz Roncari e Walnice Nogueira Galvão. For the female characters study, the critical analisys about the covered tales were very helpful, mainly, the one from Cleusa Rios. P. Passos (2000).